Metabolic fingerprinting of Arabidopsis thaliana accessions - Sotelo-Silveira, Mariana; Chauvin, Anne-Laure; Marsch-Martínez, Nayelli; Winkler, Robert; de Folter, Stefan (Frontiers in Plant Science, 2015)
In the post genomic era much effort has been put on the discovery of gene function using functional genomics. Despite the advances achieved by these technologies in the understanding of gene function at the genomic and proteomic level, there is still a big genotype-phenotype gap. Metabolic profiling has been used to analyze organisms that have already been characterized genetically. However, there is a small number of studies comparing the metabolic profile of different tissues of distinct accessions. Here, we report the detection of over 14,000 and 17,000 features in inflorescences and leaves, respectively, in two widely used Arabidopsis thaliana accessions. A predictive Random Forest Model was developed, which was able to reliably classify tissue type and accession of samples based on LC-MS profile. Thereby we demonstrate that the morphological differences among Arabidopsis thaliana accessions are reflected also as distinct metabolic phenotypes within leaves and inflorescences.